1994
DOI: 10.1246/bcsj.67.432
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction of Several Divalent Metal Ions with Benzoyltrifluoroacetone and 2-Thenoyltrifluoroacetone into Chloroform in the Presence of Tetrabutylammonium Ions

Abstract: The solvent extractions of manganese(II), iron(II), cobalt(II), nickel(II), copper(II), zinc(II), and cadmium(II) (M2+) in 0.1 mol dm−3 sodium nitrate solutions with benzoyltrifluoroacetone and 2-thenoyltrifluoroacetone (HA) into chloroform were studied in the absence and presence of tetrabutylammonium ions (tba+). The addition of tba+ enhanced the extraction, except that of copper(II). This enhancement could be explained in terms of the extraction of the ternary complex, MA3−tba+, in addition to the neutral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Figure 4 gives the results treated on the basis of Eqs. (15) and (16). As can be seen from By analyzing the data in Fig.…”
Section: Solvent Extraction Of Silver(i) With Httamentioning
confidence: 88%
See 1 more Smart Citation
“…Figure 4 gives the results treated on the basis of Eqs. (15) and (16). As can be seen from By analyzing the data in Fig.…”
Section: Solvent Extraction Of Silver(i) With Httamentioning
confidence: 88%
“…Such association constants are also reported with divalent metal ions in ref. 16 and with europium(III) in ref. 17.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that TTA forms adduct or ion-pair with trioctylphosphine oxide (TOPO) to create a synergistic effect, which increases the extraction efficiencies of metallic ions. Many researchers studied solvent extraction of metallic ions using TTA and TOPO [7][8][9][10][11][12][13][14][15][16]. Noro and Sekine [11] studied the synergistic extraction of lanthanide using TTA with TOPO or tetrabutylammonium ions (TBA ? )…”
Section: Introductionmentioning
confidence: 99%
“…and reported the distribution coefficient and equilibrium constant. Sekine et al [12][13][14][15] also performed several researches on the solvent extraction of metallic ions with the same extractants. Takazawa et al [16] reported thermodynamic study on the synergistic extraction of cobalt (II) with b-diketone and TTA.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc(II) b-diketonates and monothio-b-diketonates have also been widely studied and used as precursors for metal organic chemical vapour deposition (MOCVD) [12] where they are promising compounds for the production of high-quality films of oxide semiconductors of ZnO or ZnS [13]. b-Diketones and thio-b-diketones have also been used in solvent extraction studies of systems involving Zn(II) and other divalent metals as Cu(II), Ni(II), Cd(II) [14][15][16].…”
Section: Introductionmentioning
confidence: 99%